PDD-5S: A useful screening tool for Parkinson's disease dementia. (April 2016) - Lee, Wei-Ju; Wu, Shey-Lin; Li, Jie-Yuan; Chen, Chin-Chung; Lin, Juei-Jueng; Peng, Giia-Sheun; Lin, Tsu-Kung; Wang, Shuu-Jiun; Chen, Rou-Shayn; Yang, Yuan-Han; Tsai, Chon-Haw; Hsu, Jung-Lung; et al.
Abstract: Introduction: Parkinson's disease dementia (PDD) contributes to poor quality of life and increases the mortality risk. Early detection and diagnosis of PDD are essential for clinical care. Methods: We recruited patients with idiopathic Parkinson's disease (PD), who underwent clinical assessments and neuropsychological tests, at 12 teaching hospitals in Taiwan. Probable PDD was diagnosed according to the Movement Disorder Society Task Force clinical criteria. Using binary logistic regression, we selected significant items from an original 30-item informant questionnaire. We utilized these items, along with a simple cognitive test, to discriminate between PDD and nondemented PD (PD-ND). Results: Among the 265 PD patients (156 men, 109 women, mean age 71.9 ± 9.1 years), 102 and 163 patients were diagnosed with probable PDD and PD-ND, respectively. The mean education of participants was 8.8 ± 5.3 years, and the mean disease duration was 5.5 ± 5.4 years. When the patients fulfilled either of the following criteria: (1) a score ≥ 3 for the five endorsed screening questions, (2) a score of 1–2 for the five above screening questions combined with a score ≤ 10 items for category verbal fluency, the sensitivity and specificity of the PDD screening tool were 80.4% and 80.4%, respectively. The area under the receiver operating characteristic curve (AUC) was 0.804. We tested this screening tool in another 137 unrelated PD patients and the sensitivity, specificity, and AUC were 77.4%, 96.4%, and 0.869, respectively. Conclusion: The "PDD-5S" is a brief and useful screening tool for PDD. Highlights: We established a fast screening tool, "PDD-5S, " for Parkinson's disease dementia. We validated "PDD-5S" by executing the instrument to an unrelated patient group. "PDD-5S" has good sensitivity, specificity, and test-retest reliability. "PDD-5S" can be the first step to screen Parkinson's disease dementia patients.